AKSI IKLIM BERBASIS DIGITAL UNTUK PENGUATAN POTENSI LINGKUNGAN DESA YANG BERKELANJUTAN DI DESA KOTO MESJID - Marian Tonis; Yolanda Safitri Nelaz; Muhamad Roihan AlAzhari; Marido Bisra; Putri Rohimah (Awal Bros Journal of Community Development, 2026)
Climate change and environmental issues pose real challenges for rural communities, including in waste management and the sustainable utilization of local resources. The village of Koto Mesjid possesses significant potential in environmental conservation, fisheries, and tourism; however, this potential has not yet been supported by community awareness regarding environmental cleanliness or the optimal use of digital technology. This community service initiative aims to raise public awareness of environmental cleanliness while promoting the use of digital technology in the sustainable development of the village’s potential through digital-based climate action. The primary issues identified include suboptimal household waste management and limited use of digital media in village education and promotion. The implementation method employed a participatory approach through stages of observation, outreach, education, and hands-on practice with the community. The program included outreach and education on waste sorting, community-driven environmental cleanup activities, and the creation and distribution of posters and digital content as educational and promotional tools for the village’s potential. The target audience for the activities was the village community, village officials, and the youth as agents of change. The results of the activities indicate an increase in community knowledge and participation in maintaining environmental cleanliness, marked by the beginning of the implementation of household waste sorting and increased resident involvement in community cleanup activities. Additionally, the use of social media as a digital promotional tool has begun to develop and contribute to introducing the fisheries and tourism potential of Koto Mesjid Village. Overall, the program ran smoothly and achieved its intended objectives, although the program’s sustainability still requires consistent support from the village government and active community participation